Reliability and Safety of Cross-Leg Free Latissmus Dorsi Muscle Flap in Reconstruction of Mutilating Leg Injuries Using End-to-Side Anastomosis - Abdelmegeed, Ahmed Gaber; Hifny, Mahmoud A.; Abulezz, Tarek A.; Saied, Samia; Ellabban, Mohamed A.; Abo-Saeda, Mohamed Abdel-Al; Allam, Karam A.; Haredy, Mostafa Mamdoh; Mazeed, Ahmed S. (Archives of Plastic Surgery, 2023)
Background Free tissue transfer is considered the gold standard option for the reconstruction of distal leg defects. Free tissue transfer using recipient vessels in the contralateral leg (cross-leg bridge) is a potential option to supply the flap if there are no suitable recipient vessels in the injured leg. Most studies have described this technique using end-to-end anastomosis which sacrifices the main vessel in the uninjured leg. This study evaluated the use of a cross-leg free latissimus dorsi muscle flap for the reconstruction of defects in single-vessel legs, using end-to-side anastomosis to recipient vessels in the contralateral leg without sacrificing any vessel in the uninjured leg.Methods This is a retrospective study that included 22 consecutive patients with soft tissue defects over the lower leg. All the reconstructed legs had a single artery as documented by CT angiography. All patients underwent cross-leg free latissimus dorsi muscle flap using end-to-side anastomosis to the posterior tibial vessels of the contralateral leg.Results The age at surgery ranged from 12 to 31 years and the mean defect size was 86 cm2. Complete flap survival occurred in 20 cases (91%). One patient had total flap ischemia. Another patient had distal flap ischemia.Conclusion Cross-leg free latissimus dorsi muscle flap is a reliable and safe technique for the reconstruction and salvage of mutilating leg injuries, especially in cases of leg injuries with a single artery. As far as preservation of the donor limb circulation is concerned, end-to-side anastomosis is a reasonable option as it maintains the continuity of the donor leg vessels.
Keywords: cross-leg; end-to-side anastomoses; free latissimus dorsi flap; single-vessel leg; mutilating leg injuries